Perancangan Alat Pemotong Tulang Daging Dengan Chainsaw Skala Industri Rumahan - Albert Daniel Saragih; Muhammad Rifqi Aliftyo; Deni Mulyana (Piston: Journal of Technical Engineering, 2022)
The technique of bones saw was used by many traders still uses the conventional method, namely with a butcher knife. To make cutting more efficient, bone saw machines are created which are widely marketed. However, the use of these tools is considered inefficient because during operation the meat attached to the bones will move into the machine through the cutting tool so that the motor work becomes heavy and even the cutting tools are prone to breaking, then the electrical power required is large enough to make traders use more conventional methods. This manufacturing technique aims to produce designs and working drawings of meat bone cutting machines and the components needed. Bone cutting machines are designed to be used by various groups of bone traders, market traders or home-based traders to increase production and use low electrical power. The machine was designed to be more efficient than the previous by modifying the cutting tool using a saw type, namely a chainsaw with a low electrical power of 550 Watt or equivalent to 0.75 HP and a blade speed of 2500 rpm. The machine was designed to use a spring to raise the machine automatically. The dimension of 800 mm × 700 mm × 1415 mm has double safety that is protected by a cover and a lever to provide distance between the machine and the operator.